Trio Album for violin, violoncello & piano, vol. V Violin part - BARGIEL, Waldemar [et.al] (The Boston Music Co.)
LentonThe bellsnRomance sans parolesnEpithalamenBoleronBarcarollenSerenadenWaltz-ScherzonCanzonetta